Fingerprint database - Nur Amira, Ariffin (2015)
This project aims to save a fingerprint in the database. Fingerprints contain many details, which are known as minutiae, that can be used for identification marks in fingerprint verification. Fingerprint recognition is one of the biometric techniques. Each person has a different pattern of fingerprint make it unique and different from each other. Therefore, it can be used for personal identification. Using fingerprint recognition makes a guarantee to be more secure because of unchangeable fingerprint. There are many applications that used fingerprint recognition like fingerprint recognition to replace password and also used fingerprint recognition to recognize the individual identity card for a long period. This project needs the user to thumbprint their finger to be save in database and later their fingerprint is compared and match to retrieve the information.